Antidepressant dose and treatment response in bipolar depression: Reanalysis of the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) data. (September 2015) - Tada, Mitsuhiro; Uchida, Hiroyuki; Mizushima, Jin; Suzuki, Takefumi; Mimura, Masaru; Nio, Shintaro
Abstract: The aim of this study is to evaluate whether an adjunct antidepressant therapy at a higher dose to a mood stabilizer would make a difference in the treatment of bipolar depression. This is a post-hoc analysis of the data from the randomized treatment for acute depression of the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD), in which patients with bipolar depression were randomly assigned to treatment with a mood stabilizer plus adjunctive antidepressant drugs or placebo. According to the highest dose received in the course of treatment, the subjects were divided into one of the following three groups: high-dose, low-dose and placebo groups. The primary and secondary outcomes were durable recovery (which was operationally defined as eight consecutive weeks with </ = 2 symptoms) and treatment-emergent affective switch (i.e. transition to mania or hypomania), respectively. In the evaluable 333 subjects, subjects in both the high-dose (n = 102) and placebo groups (n = 169) more significantly achieved durable recovery than the low-dose group (n = 62) (odds ratio = 3.013 [p = 0.009], 2.899 [p = 0.008], respectively). No significant association was found between the dose status and treatment-emergent affective switch (p = 0.614). The allocation to either high- and low-dose antidepressants was not randomized and the dose was guided by a case-by-case decision, which hampers to draw a firm conclusion on dose–response issues and renders the findings as preliminary. Nevertheless, higher doses of adjunctive antidepressant drugs seem to have potential for yielding greater clinical improvement without increasing any risk of manic switch compared to lower doses, at least in carefully selected patients. The ClinicalTrials.gov identifier: NCT00012558 . Highlights: Effects of adjunctive antidepressant dose were evaluated in bipolar depression. Subjects receiving higher antidepressant dose more frequently recovered. No significant association was found between the dose and affective switch. Higher adjunctive antidepressant dose may yield greater clinical improvement.